STUDI FAKTOR PENENTU KINERJA KARYAWAN PT. HASJRAT ABADI PALU - Syamsul, Syamsul; Muhammad, Fadel (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2020)
This study aims to determine the effect of work environment, work culture, work motivation, job satisfaction, work discipline, and work stress on employee performance. This type of research is quantitative research. The research sample was 63 employees of PT. Hasjrat Abadi Palu. The results of regression analysis show that the work environment, work culture, job satisfaction, and job stress partially have a positive and significant effect on employee performance. Meanwhile, work motivation and work discipline do not have a significant effect on employee performance. The results can be used as a source of information in determining company policies to improve employee performance. In addition, these findings can be used as a reference for further research interested in discussing employee performance.